Etika Birokrasi Di Dinas Kependudukan Dan Catatan Sipil Kabupaten Bone - Fitri, Fitri; Razak, Andi Rosdianti; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study aimed to know Bureaucratic Ethics in the population and civil registry office of bone Regency. This study used qualitative research. The number of informants in this study were 2 peopleusing intervew techniques. The type of data used primary and secondary data, these two types of data could be obtained by observation, interviews and documentation. Data analysis techniques was a sace study research method. The result of this study showed that the service was still lacking and service ethnics still needed to be improved,  some people who did not care about  morality. It was important to apply ethics in terms of service so that people werw satisfied with the service.  Keywords: Bureaucratic Ethics, population and civil registration This study aimed to know Bureaucratic Ethics in the population and civil registry office of bone Regency. This study used qualitative research. The number of informants in this study were 2 peopleusing intervew techniques. The type of data used primary and secondary data, these two types of data could be obtained by observation, interviews and documentation. Data analysis techniques was a sace study research method. The result of this study showed that the service was still lacking and service ethnics still needed to be improved,  some people who did not care about  morality. It was important to apply ethics in terms of service so that people werw satisfied with the service.  Keywords: Bureaucratic Ethics, population and civil registration